2009
DOI: 10.1111/j.1460-9592.2009.03043_9.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of paediatric caudal extradural anaesthesia practice

Abstract: Introduction:  Caudal extradural anaesthesia (CEA) is a common technique with wide application in paediatric anaesthesia [1]. An ‘on line’ World Wide Web survey of paediatric anaesthetists was undertaken to delineate any differences in the practice of this procedure. Methods:  A web based questionnaire was devised to survey the practice of caudal extradural anaesthesia in children by anaesthetists who were members of the Association of Paediatric Anaesthetists of Great Britain and Ireland (APAGBI). The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…6 Several additives including clonidine and ketamine have been investigated to improve analgesic efficacy and reduce local anaesthetic dose. In a recent survey of paediatric caudal anaesthesia practice in the UK and Ireland, an increased use of ketamine from 32% (2002) 2 to 37.5% (2009) 7 was reported. In contrast, the use of neuraxial ketamine for paediatric anaesthesia in Germany and Switzerland was not recommended 33 due to an ongoing discussion about a potential neurotoxicity of ketamine observed after repeated intrathecal ketamine in rats, mice, and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several additives including clonidine and ketamine have been investigated to improve analgesic efficacy and reduce local anaesthetic dose. In a recent survey of paediatric caudal anaesthesia practice in the UK and Ireland, an increased use of ketamine from 32% (2002) 2 to 37.5% (2009) 7 was reported. In contrast, the use of neuraxial ketamine for paediatric anaesthesia in Germany and Switzerland was not recommended 33 due to an ongoing discussion about a potential neurotoxicity of ketamine observed after repeated intrathecal ketamine in rats, mice, and rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been proved that several additives with local anesthetics can prolong the duration of caudal analgesia [ 3 ]. Research discovered that the most commonly used additives were clonidine (42.3%), ketamine (37.5%), opioids (18.1%), adrenaline (1.8%), and midazolam (0.3%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, we surveyed members of the Association of Paediatric Anaesthetists of Great Britain and Ireland to assess whether their aseptic technique before caudal epidural procedures had changed after Menzies et al. 's survey and publication of the AAGBI's infection control guideline in 2008 . This guideline also suggested that anaesthetists should use full surgical asepsis for all neuraxial procedures, including caudals, even though Menzies et al.…”
mentioning
confidence: 99%